Identification of Microplastics Content in Sediment, Water and Digestive Channel of Milkfish (Chanos chanos) in Sidoarjo Pond - Annisa Inda Sanabila; Moch Irfan Hadi; Atiqoh Zummah (Al-Hayat: Journal of Biology and Applied Biology, 2022)
Microplastics are a form of new pollution that the Indonesian people are not aware of. The factors for the entry of microplastics into pond waters are water sources, anthropogenic activities, and pond cleanliness. The purpose of this study was to determine the abundance of microplastics, the color and shape of microplastics, and the types of microplastic polymers found in sediment, water, and the digestive tract of milkfish (Chanos chanos) in Sidoarjo ponds. The average abundance of microplastics in sediment samples obtained from semi-intensive ponds is 300 particles per 50 grams, while the sediment samples from traditional ponds are 613 particles per 50 grams. The average abundance of microplastics in the semi-intensive pond water samples was 2.1 particles per 20 liters and in traditional ponds was 2.3 particles per 20 liters. The average abundance of microplastics in the milkfish (Chanos chanos) samples from the Semi-Intensive Pond was as many as 6 particles per tail, while the Traditional Pond had 9.5 particles per tail. In this study, four colors of microplastics were found, namely blue, black, red, and transparent, while the microplastics obtained were fiber, fragment, and filament. The types of microplastic polymers encountered in this study were dominated by polyamide or nylon polymers. In sediment samples from both ponds, we found the presence of Polyamide or Nylon polymers, namely Polystyrene and Polyamide or Nylon, and in the digestive tract of milkfish (Chanos chanos), namely Polyamide or Nylon.